Assessing aggregate welfare: growth and inequality in Argentina - Gasparini, Leonardo (2000)
This paper has two main goals. The first is to complement the Argentine mean income series with inequality estimates in order to obtain aggregate welfare series. Average income figures are estimated from National Accounts while income inequality indices are calculated from the Permanent Household Survey (EPH). Household income from the survey is adjusted for nonresponse, underreporting and demographics. The second objective of the article is to check the statistical significance of changes in inequality and welfare measures. Bootstrapping techniques are used to that aim. One of the main conclusions is that while welfare assessments coincide among different value judgments in some periods (e.g. 1991-1994), they widely vary in some others, particularly in the last four years (1994-1998), where the economy experienced moderate growth and large increases in inequality. It is argued that the period 1994-1998 provides an unprecedented laboratory for distinguishing the social preferences of different analysts according to their evaluation of the performance of the Argentine economy.